2016
DOI: 10.1007/s10545-016-9980-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of blood biomarkers with age informs pathomechanisms in succinic semialdehyde dehydrogenase deficiency (SSADHD), a disorder of GABA metabolism

Abstract: We hypothesized that blood levels of GABA and γ-hydroxybutyric acid (GHB), biomarkers of succinic semialdehyde dehydrogenase deficiency (SSADHD), would correlate with age. GABA and GHB were quantified in plasma and red blood cells (RBCs) from eighteen patients (age range 5–41 years; median 8). Both metabolites negatively correlated with age (P<0.05). Plasma and RBC GHB declined with age, reaching a nadir and approximate steady-state by 10 years. Declining plasma GABA achieved this approximate steady state at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…To answer this question, a longitudinal analysis of brain GHB in patients (either employing cerebrospinal fluid, or methods to quantify GHB in vivo using edited magnetic resonance spectroscopy) will be needed. Nonetheless, surrogate studies to date (hair, plasma, red blood cell GHB content) all point to an age-dependent lowering of GHB in brain in SSADHD (Jansen et al 2016). It is important to point out that no negative correlation of GHB vs. age was observed in unaffected controls.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To answer this question, a longitudinal analysis of brain GHB in patients (either employing cerebrospinal fluid, or methods to quantify GHB in vivo using edited magnetic resonance spectroscopy) will be needed. Nonetheless, surrogate studies to date (hair, plasma, red blood cell GHB content) all point to an age-dependent lowering of GHB in brain in SSADHD (Jansen et al 2016). It is important to point out that no negative correlation of GHB vs. age was observed in unaffected controls.…”
Section: Discussionmentioning
confidence: 96%
“…In an effort to explore metabolic developmental characteristics, we recently quantified GABA and GHB in plasma and red blood cell (RBC) lysates obtained from a cohort of 18 patients (age range 5-41 years; median 8 years) and found that both compounds negatively correlated with age (Jansen et al 2016). In that study, plasma and RBC GHB levels reached a nadir and approximate steady-state by 10 years of age, whereas plasma GABA achieved an approximate steady state level at 30-40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…Succinic semialdehyde dehydrogenase (SSADH) deficiency (SSADHD) is a rare disorder on the GABA metabolic pathway. The product of glutamate decarboxylation, GABA is catabolized to succinic acid in a two-enzyme sequence, including generation of succinic semialdehyde (SSA) catalyzed by GABA-aminotransferase and the further oxidation of SSA to succinic acid catalyzed by SSADH [ 10 ]. The backbone of GABA thus enters the tricarboxylic acid cycle for further metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in plasma and RBC samples derived from SSADHD patients identified age-dependent negative correlations for both GHB and GABA [ 10 ]. GHB in plasma reached a nadir at approximately the age of puberty (~ 13–16 years of age), while the same nadir for GABA occurred well into the 3rd decade of life.…”
Section: Introductionmentioning
confidence: 99%
“…The mouse model of SSADH deficiency has provided valuable avenues from which to explore additional preclinical therapeutics targeting SSADHD, including NCS-382 (a GHB receptor antagonist), neuroactive steroids, and agents that inhibit the mechanistic target of rapamycin [ 4 , 8 11 ]. The SSADHD mouse has facilitated the collection of outcome data such as survival, electrophysiology, metabolite levels and gene expression [ 3 , 10 , 12 ]. The latter has focused our interest on the capacity of mTOR inhibitors to extend the survival of aldh5a1 -/- mice in vivo.…”
Section: Introductionmentioning
confidence: 99%